A conceptual model for facilitating learning from physics tasks using visual cueing and outcome feedback: theory and experiments - Agra, Elise Stacey Garasi (Kansas State University, 2015)
This dissertation investigates the effects of visual cueing and outcome feedback on students' performance, confidence, and visual attention as they solve conceptual physics problems that contain diagrams. The research investigation had two parts. In the first part of the study, participants solved four sets of conceptual physics problems that contain diagrams; each set contained an initial problem, four isomorphic training problems, a near transfer problem (with a slightly different surface feature as the training problems), and a far transfer problem (with considerably different surface feature as the training problems). Participants in the cued conditions saw visual cues overlaid on the training problem diagrams, while those in the feedback conditions were told if their responses were correct or incorrect. In the second part of the study, the same students solved the near and far transfer problems from the first study two weeks later. We found that the combination of visual cueing and outcome feedback improved performance on the near transfer and delayed near transfer problems compared to the initial problem, with no significant difference between them. Thus, the combination of visual cueing and outcome feedback can promote immediate learning and retention. For students who demonstrated immediate learning and retention on the near and far transfer problems, visual cues improved the automaticity of extracting relevant information from the transfer and delayed transfer problem diagrams, while outcome feedback helped automatize the extraction of problem-relevant information on the delayed far transfer problem diagram only. We also showed that students' reported confidence in solving a problem is positively related to their correctness on the problem, and their visual attention to the relevant information on the problem diagram. The most interesting thing was how changes in confidence occurred due to outcome feedback, which were also related to changes in accuracy and visual attention. The changes in confidence included both reductions in confidence and increases in confidence due to feedback when the student was wrong (first) and right (later). This seems to have led to learning (change in accuracy), and also changes in attentional allocation (more attention to the thematically relevant area).
Keywords: Physics education; Problem solving; Visual attention; Outcome feedback; Automaticity; Physics (0605); Science Education (0714)